Incidencia de la política pública en la generación de centros nutricionales para disminuir el sobrepeso u obesidad, cantón Quevedo, provincia de Los Ríos - Posligua Cabrera, Marjorie Janeth (2015)
This thesis is focused on determining the impact of public policy in generating nutritional centers to reduce overweight or obesity, Quevedo Canton; for which various research techniques that allowed the collection of information relating to overweight and its impact on the daily life of the population that the bears were used; it based on research results is presented as proposed, a program of inspection and monitoring care consultations to people, especially to those who are overweight or obese. Proposal is related to the various programs promoted by the Ministry of Health, as the governing body of the National Health System; to minimize chronic diseases in users of health houses of different types of care, this program allows control and monitoring provide a better quality of life, and ideal food style. Currently, the problems of overweight and obesity have become very important for its high incidence and its consequences on the health of the population; for which to date have intensified several campaigns of state policies for this group of priority attention, established and promoted by the Ministry of Public Health in regard to health has greatly improved the physical infrastructure and equipment of houses health, greater investment in health professionals, therefore in family physicians to achieve greater extramural have coverage, increased vaccination campaigns, as well as frequent monitoring policies exist in the various campaigns both motherhood, immunizations, labeling products, aspects that are executed according to the provisions of the Manual of Comprehensive Health Care, as being primary care health the gateway to the NHS, it is in these Operating and offices where units focuses the as many health care to the population. To minimize chronic diseases in users of health houses of different types of care, allowing this control and monitoring program providing a better quality of life, and ideal food style.